LIFE CYCLE AND MORPHOLOGICAL CHARACTERISTICS OF WEEDY RICE (ORYZA SATIVA COMPLEX, LOCALLY CALLED PADI ANGIN), A NOXIOUS WEED OF RICEFIELDS IN MALAYSIA - Zainal Abidin Abd Hamid; Mashhor Mansor; Azmi Man (Tropical Life Sciences Research, 2007)
Studies were conducted at the plant house and the laboratory at the School of Biological Sciences, Universiti Sains Malaysia (USM), Pulau Pinang to evaluate seed germination, seedlings establishment and growth patterns Oryza Sativa of (weedy rice). Weedy rice is rated as one of the most troublesome weeds in direct seeded fields in Malaysia. Evidently, there are 10 variants of weedy rice based on morphological characteristics. Morphological structures of weedy rice namely open panicle type, compact panicle type, and awn type were examined. The comparison using scanning electron microscope (SEM) did not show anatomical differences between weedy rice variants for both seed and leaf surfaces. However, the hair or trichomes structures are clearly shown in awn type compared with other variants and Oryza Sativa (cultivated rice). Cultivated rice and all variants have stomata on both adaxial and abaxial leaf surface. However, more dense deposits of epicuticular waxes were found on the adaxial surface of a leaf compared with the abaxial surface. The result of growth pattern showed that the variants of weedy rice produce an abundance seeds, as high as 200–220 numbers of spikelets per panicle for awn type, 190–210 spikelets for open panicle type and 210–230 spikelets for compact panicle type. All variants complete their life cycles within 85–95 days after emergence. Kajian telah dijalankan di rumah tumbuhan dan makmal di Pusat Pengajian Sains Kajihayat, Universiti Sains Malaysia (USM), Pulau Pinang terhadap percambahan biji benih, pembentukan biji benih dan corak pertumbuhan Oryza Sativa complex (padi angin). Padi angin merupakan salah satu rumpai yang bermasalah dalam penanaman padi tabur terus di Malaysia. Terdapat sepuluh varian padi angin berdasarkan ciri-ciri morfologi, iaitu jenis tangkai terbuka, tangkai tertutup dan jenis yang mempunyai jejanggut. Perbandingan melalui mikroskop elektron pengimbas (SEM) tidak menunjukkan perbezaan anatomi antara varian padi angin terhadap biji dan permukaan daun. Walau bagaimanapun, struktur rerambut jelas kelihatan pada jenis jejanggut berbanding varian yang lain dan Oryza Sativa (padi biasa). Padi biasa dan semua varian mempunyai stoma di kedua-dua belah permukaan daun, adaksial dan abaksial. Namun, kepadatan epicuticular waxes banyak terdapat di bahagian adaksial permukaan daun berbanding bahagian abaksial. Padi angin menghasilkan biji yang banyak, iaitu 220–220 biji per tangkai bagi jenis jejanggut, 190–210 biji bagi tangkai terbuka dan 210–230 biji bagi tangkai tertutup. Semua varian melengkapkan kitar hidup dalam masa 85–95 hari selepas bercambah.